EFFECT OF PULSED ELECTRO MAGNETIC FIELD (PEMF) EXPOSURE OF CHICKEN HATCHING EGGS ON HATCHABILITY PERFORMANCE - C. Pandian; A.V. Omprakash; R. Richard Churchil; A. Sundaresan; M. Babu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The above study was conducted to analyze the hatchability performance of broiler breeder hatching eggs at Institute of Poultry Production and Management, Tamil Nadu Veterinary and Animal Sciences University (TANUVAS), Chennai – 51.  A total of 4436 broiler breeder hatching eggs with 12 settings were divided in to two equal groups of each 2218 as treatment and control. The treatment group hatching eggs were exposed to PEMF at 1Hz frequency with 1500 nT intensity for 18 hours at 180 C and 80 percent relative humidity. The control eggs were stored at the same temperature and humidity but kept unexposed to the PEMF.  After bringing into room temperature for one hour, the eggs were incubated under optimum temperature and humidity in setter and hatcher. The hatchability performance showed no significant difference between treatment and control groups. Percent hatchability to total and fertile egg set for treatment group were 76.09 and 90.36 and that of control were 73.89 and 89.59 respectively. There were no  significant differences observed for mean per cent embryonic mortality, mean per cent dead in germ and dead in shell between treatment and control group. The results of this study provide enough indication from the experiment, that it is imperative to conduct a few more trials using a different combination of frequency, intensity and dose duration to get better hatchability performance.